Treatment of gynecomastia with prednisone: case report and literature review - Jin, Yansheng (J Int Med Res, 2019)
This study aimed to report a unique case of primary adrenal insufficiency that was accompanied by painful gynecomastia, which was resolved by treatment with prednisone. Enlargement of the left breast with continuous weakness and generalized nausea in a male was discovered 3 months before admission. Magnetic resonance imaging of the brain was normal 1 month before presentation. A physical examination revealed that the diameter of the left breast was 5 cm and the height was 3 cm. Laboratory investigations revealed hyponatremia, with a low serum cortisol level and an elevated prolactin level. Hyperprolactinemia was suspected because of adrenal deficiency that was directly or indirectly associated with increased prolactin levels. Thus, a diagnosis of hyperprolactinemia was confirmed. Ultrasonography of the left breast showed glandular tissue hyperplasia. In the present study, treating adrenal insufficiency with prednisone relieved both gynecomastia and hyponatremia. However, gynecomastia regression and hyponatremia resolution were observed when prednisone was stopped. Gynecomastia completely resolved by re-administering prednisone. Therefore, treating the underlying disease is essential so that prednisone can be given in a timely manner.